Protective ability of melanoidins on riboflavin photo-degradation - Thu Trang, Vu; Xuan Thanh, Lam (Vietnam Journal of Science and Technology, 2017)
Effects of melanoidins, Maillard reaction products, on riboflavin photo-degradation were studied in riboflavin solution (1.5 mg L-1) and Ultra high temperature treated milk (UHT-treated milk) during exposure to irradiation at 7000-lux light intensity for 2.5 h. In riboflavin solution, melanoidins showed the protective ability on the degradation of riboflavin under light exposure, and this ability depended on melanoidins concentration. In addition, the protective ability of melanoidins was higher than that of ascorbic acid which has the ability to reduce riboflavin photo-degradation. The study on milk sample clarified that heat-treatment of milk enhanced the protective ability on the riboflavin photo-degradation. Thus, it could be concluded that melanoidins were compounds which were responsible for the riboflavin photo-stability in UHT-treated milk.